2021
DOI: 10.1097/jhq.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Practicing What We Teach: Increasing Inhaler Use for Mild Asthma in the Pediatric Emergency Department

Abstract: Introduction: Asthma is a leading cause of pediatric emergency department (ED) visits. A metered-dose inhaler and spacer (MDI-S) device is equivalent to and more cost effective than delivery by nebulization in the ED management of mild asthma exacerbations. We aimed to increase the use of albuterol MDI-S among patients with mild asthma exacerbations using a quality improvement framework. Methods: We evaluated albuterol use for mild asthma exacerbations between January 2019 and March 2020 in our pediatric EDs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Order set use is a part of standard practice in the ED at our institution and has been utilized to implement prior QI efforts. 19 We successfully leveraged the existing culture at our institution to implement this practice change recommendation. Standardization of care via order set use has been shown to drive practice for other disease processes at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Order set use is a part of standard practice in the ED at our institution and has been utilized to implement prior QI efforts. 19 We successfully leveraged the existing culture at our institution to implement this practice change recommendation. Standardization of care via order set use has been shown to drive practice for other disease processes at other institutions.…”
Section: Discussionmentioning
confidence: 99%
“…provider skepticism that MDI-spacer was as effective as nebulizer use). Furthermore, there are cost and logistic considerations associated with combined albuterol-ipratropium delivery, which are unique when needed for moderate asthma exacerbation [27 ▪ ]. Facilitators to MDI-spacer use included attributes of the practice environment (i.e.…”
Section: Implementation Of Clinical Practice Guidelinesmentioning
confidence: 99%
“…On the contrary, using a quality improvement framework that involved an electronic order set prioritizing albuterol MDI-spacer as well as educational initiatives, Agbim et al [27 ▪ ] found that albuterol delivery via MDI-spacer for treatment of mild paediatric asthma exacerbations in their pediatric ED notably increased from 34.4 to 47.7%. There was no associated change to length of stay in the ED or need for hospital admission.…”
Section: Implementation Of Clinical Practice Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the success that previous pediatric hospitals had using revised clinical pathways in the EHR to standardize care for commonly treated disease processes, we determined that adapting this implementation strategy in addition to educational initiatives would work best for our hospital. [11][12][13]…”
Section: Introductionmentioning
confidence: 99%